The effect of supervisors' safety leadership styles on workers' safety behaviours in SME manufacturing firms - Nur Syifa, Mohamad Zahir (2021)
Incline accident trend in Malaysia indicate the need to enhance safety behaviour intervention. Hazard and pathogen are already exist in our environment; however, an accident is triggered by human unsafe behaviour. It indicates insufficient or ineffective safety behaviour employed in an organization. The highest accident rate contribution is derived from SMEs sector which accounted 80%. Besides, SMEs contributes highest GDP (5.8%) towards Malaysia economy. These two elements urged the need for safety behaviour study in SMEs sector. The research objective is to investigate the relationship between Leader-Member Exchange (LMX) and empowering leadership towards safety participation and safety compliance among employees in SMEs manufacturing firms. It was conducted towards organization level represented by Safety & Health Officer, Safety & Health Coordinator, Safety & Health Representative or Human Resource Officer in Northern state SMEs manufacturing firms. This study employs quantitative design field study with crosssectional time frame. The analysis of data collection has been performed by statistical tool Statistical Program for Social Science (SPSS) version 26 and Partialleast-squares structural equation modelling (PLS-SEM) Smart PLS version 3.0. A significant relationship has been outlined for LMX safety leadership towards safety participation and safety compliance. In addition, a significance relationship also has been outlined for empowering safety leadership towards safety participation and safety compliance.